Constructions of Homophobic Hate Crimes: Definitions, Decisions, Data - Tiby, Eva (Journal of Scandinavian studies in criminology and crime prevention, 2007)
A study on reported crimes has been conducted in order to broaden the knowledge concerning homophobic hate crimes in Sweden. What happened between whom, where, and when? And what did the reports result in? Hate crimes are to be prioritized by the criminal justice system; does this actually happens, and is the clause governing increased sentence severity in the Penal Code applied? Above all, the study focuses on the issue of what constitutes a hate crime, and on the actors who constructs hate crimes. The study is based on police-recorded offences, assumed by the police to be hate crimes. A good half of the 614 reports recorded 2004 is included and followed up through the criminal justice system. The results are presented by typical cases and display that the events just as often occur between acquaintances as between strangers, that the suspects generally speaking are quite young, approximately 25% have not reached the age of criminal responsibility. The arenas are public places, the home, schools, places of amusement, as well as the Internet, cellphones, and similar media. Less than 10% of the reported offences end up as verdicts. This is due to, of course, the fact that the demands for an offence to be registered by the police are much less rigorous than the demands made on a case to result in a verdict. But apart from 'natural legal waste' in terms of misunderstandings, meagre information, and difficulties to produce evidence, there is an extra factor added in these cases. It seems that the police apply a more inclusive definition of 'hate crime' compared to prosecutors and courts. While the former register 'homophobic hate crimes', where 'anyone' can be a victim, the latter use the more narrow concept of 'hate crimes against homosexuals'. Thereby treating a negligible amount of the reports as hate crimes